Relationship between Environmental Degradation, Resource Scarcity, and Civil Conflicts in Somalia - MOHAMED, Abdinur Ali; NAGEYE, Ahmed Ibrahim (Journal of Environmental Management and Tourism, 2019)
The purpose of this study was to examine relationship between environmental degradation, resource scarcity, and civil conflict in Somalia. Environmental degradation is disposed to increase the number of disputes emerging from duel over the scarce resources. Consequently, it makes the society such offensive that it is inclined to armed conflict. In this study we investigated five variables in which civil conflict was the dependent variable. Population growth, land degradation, water resource and the climate change were explanatory variables. Time series data, 1990-2015, from various sources was employed. Regression methods, Ordinary Least Square was used to estimate the model parameters. Augmented Dickey-Fuller test was used to examine stationary of the data as Johansen cointegration was used to detect the long run relation between the study variables. The study found that one million increase of the rural population will lead the likelihood of the civil conflicts by about 1.04%. The decline of every one hector of arable land will cause the likelihood of the civil conflict to increase by about 1.5%. The rise of the one kilometer cubic of fresh water decreases the likelihood of the civil conflicts to about 4.49%. Rise of the temperature came to be insignificant and has no contribution to the civil conflicts in Somalia.